Professional Competence of Future Mathematician and its Components - Samaruk, Nataliya; Poplavska, Olena (Pedagogical Discourse, 2017)
According to the law of Ukraine on higher education one of the requirements for education and training program is to highlight the list of competences future graduates. So important is the need for the definition of what constitutes «professional competence» future mathematician, list of competencies and learning outcomes that should have graduate. Therefore requires special study the problem of formation of professional competence of students of mathematical specialties. The problems of professional training for future mathematicians are discussed in the article. The relevance of the formation of professional competence of students of mathematical specialties is justified. Basic principles and definitions of the competence approach are considered in the article. The essence of the concept of «professional competence» of the future mathematician is defined. The structure of professional competence of future mathematicians is clarified on the basis of the analysis of scientific literature: epistemological (mathematical knowledge, ownership modeling techniques), activity (the skills of application of the mathematical knowledge to solve problems of professional activity), motivation (the motives, goals, need for professional growth, improvement and self-development in the profession). The components of professional competence are singled out, which are interrelated and mutually complementary. Classification of competences of the future mathematician is carried out. Own approach to the definition of the components of professional competence of future mathematicians is presented. The components of the professional competence of future mathematics are defined: analytical and research, technological, prognostic, technical, organizational and managerial, social-personal, systemic, information. The list of competencies and learning outcomes that a graduate of the specialty «Mathematics» should possess is given. Key words: preparation of future mathematicians, competence, professional competence of future mathematicians, structure and components of professional competence of mathematicians.